PRODUCTION OF VERMICOMPOST BY UTILIZING PADDY (ORYZA SATIVA) STRAW (PRE-DIGESTED WITH TRICHODERMA VIRIDE) AND EUDRILUS EUGENIAE, PERIONYX EXCAVATUS AND LAMPITO MAURITII - J.VIJI; P. NEELANARAYANAN (International Journal of Pharma and Bio Sciences, 2013)
The paddy straw is one of the most abundant agricultural by-products in Tamil Nadu, India. It contains approximately 37% cellulose, 24% hemicelluloses and 15% lignin. In the present investigation the paddy straw was pre-digested with Trichoderma viride and subsequently the same was utilized for the production of vermicompost by using Eudrilus eugeniae, Perionyx excavatus and Lampito mauritii under monoculture conditions.The conversion ratio of waste into vermicompost was found to be high (71%) in the trays in which E. eugeniae was used. Further, it was observed in the end product the E. eugeniae produced more number of cocoons and young ones when compared to the other two cultures. The vermicompost harvested from E. eugeniae experimental trays showed remarkable levels of chemical nutrients and higher density of microbial population viz., Bacteria, Actinomycetes and Fungi than the other experimental trays. The results of the present study apparently suggest that in though all the three earthworm species can be used for converting paddy straw (pre-digested with T. viride) into value added vermicompost, E. eugeniae in is very effective.